Approach to the diagnosis and treatment of non-tuberculous mycobacterial disease. (August 2021) - Pennington, Kelly M.; Vu, Ann; Challener, Douglas; Rivera, Christina G.; Shweta, F.N.U.; Zeuli, John D.; Temesgen, Zelalem
Abstract: Non-tuberculous mycobacteria (NTM) is a collective name given to a group of more than 190 species of Mycobacterium . The clinical presentation for most NTM infections is non-specific, often resulting in delayed diagnosis. Further complicating matters is that NTM organisms can be difficult to isolate. Medications used to treat NTM infection can be difficult for patients to tolerate, and prolonged courses of anti-mycobacterial therapy are often required for adequate suppression or eradication. Herein, we review different NTM syndromes, appropriate diagnostic tests, and treatment regimens.